PENGARUH KUALITAS PRODUK, HARGA, DAN SOCIAL MEDIA MARKETING TERHADAP KEPUTUSAN PEMBELIAN PADA PRODUK PUYO SILKY DESSERT DI JAKARTA SELATAN - Sekar Jati, (2022)
This study aims to find out and prove the influence of product quality, price, and social media marketing on the purchasing decision of puyo dessert products. This research is a quantitative study with primary data sources. The population in this study is consumers or people who have purchased Puyo dessert products in South Jakarta. The sample used was 100 respondents, using the non probability sampling (purposive sampling) method. Data analysis technique using Partial Least Square (PLS) with SmartPLS 3.0 software. The results of this study show that there is a positive and significant influence of product quality, price, and social media marketing variables on purchasing decision variables. Based on the T-statistical test, the most influential variable was obtained, namely social media marketing of 0.472 while the product quality variable had an influence of 0.240 and the price variable had an influence of 0.192. From the results of the research, Puyo Dessert should be able to maintain and improve social media marketing and improve the quality of its products to be able to increase sales through purchase decisions.